STUDI DESKRIPTIF MUSIK TRADISIONAL LAGIA PADA KEBUDAYAAN NIAS DI SANGGAR MUSEUM PUSAKA NIAS KOTAMADYA GUNUNGSITOLI - Priska Eunike Putri Zebua (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
ABSTRACT            This study aims to determine the descriptive study of Lagia traditional music in Nias culture at the Museum Pusaka Nias. The approach tha the authors take is to use qualitative research methods. The work process carried out namely, observation, interviews, documentation, recording of activities, song transcript. This research was conducted by gathering information through field research to obtain results that are processed into original data.            The results of the research show that Lagia is a single-stringed musical instrument made from salak roots, with a resonator made from sugar palm sticks, strings handles made of palm sugar pieces, strings made of tutura (rattan) and bow made of wood that has supple properties liek bamboo which are classified into the Chordophone classification. The author determines the location in the Museum Pusaka Nias and interview figures who ubderstand and understand it in that field. Lagia musical instrumen is played by using a bow which firts strings and both bow strins must be smeared with water (in the old days using saliva).Keywords : Descriptive study, Traditional Music, Lagia